Kualitas Spermatozoa Babi dalam Pengencer Air Buah Lontar dan Kuning `Telur Ayam Kampung dengan Metode Penyimpanan yang Berbeda - Maria Selviana Bebbe Bei; Nancy D F K Foeh; Cynthia Dewi Gaina (Jurnal Veteriner Nusantara, 2021)
The aim of this study is to find the best concentration ratio of native chicken egg yolk (NCEY) and lontar water (LW) in order to preserve landrace boar semen, with water jacket and non-water jacket method, at 5°C and to find how long can it preserve the semen. Fresh semen was collected from Landrace boar 2-4 years old age. Semen sample is categorized apropriate to be extended if >70% sperm motility, >200x106 cells/ mL, and >20% sperm abnormality. This study was designed with compeltely ranomized design and faktorial patern with 2 controled group, 6 treated group, and 4 repitition. Controled group consist of fresh semen without extender. K0 was preserved with non-water jacket method, and K1 was preserved with water jacket method. Controled group were P1 (95% LW + 5% NCEY), P2 (85% LW + 15% NCEY), P3 (75% LW + 25% NCEY) that preserved with water jacket method, and P4 (95% LW + 5% NCEY), P5 (85% LW + 15% NCEY), P6 (75% LW + 25% NCEY) preserved with non-water jacket method. Sperm motility and viablity were evaluated every 2 hours until motility value has reached 40%. The result shows that P2 is the best concentration to preserve sperm motility (26 hours, 45.00±0.00%) and viability (30 hours, 51.00±0.40%).